Vision Redux: Power and Policy in Saudi Arabia - Kimm, Ross Douglas (AUC Knowledge Fountain, 2021)
The size and scope of the Vision 2030 modernization plan and the associated Saudi Aramco initial public offering are watershed events in the history of the modern Kingdom of Saudi Arabia. However, they are not outside the history of the country’s development. This thesis, tracing the roots of this latest development plan back to the founding of the current Saudi state, found that Vision 2030 shares many characteristics with previous efforts. Further, it also found precedence for powerful princes rising to power at times of tectonic change. Finally, while historical context is key to understanding this moment in the Kingdom, this thesis argues that Vision 2030 is best considered a subset of Mohammad bin Salman’s rise to power.